2013
DOI: 10.1016/j.neuint.2013.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of central β2-adrenoceptors suppresses NFκB activity in rat brain: A role for IκB

Abstract: In this study we examined the impact of systemic treatment with the long-acting brain penetrant β2-adrenoceptor agonist clenbuterol on NFκB activity and IκB expression in rat brain. Clenbuterol decreased NFκB activity (p65 DNA binding) in nuclear extracts prepared from rat cortex and hippocampus for up to 8h following a single treatment. This was accompanied by increased expression of IκBα mRNA and protein. The temporal increase in IκB protein expression paralleled the suppression of NFκB activity, suggesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 50 publications
1
12
2
1
Order By: Relevance
“…In line with this, b 2 -AR agonists have been proposed as therapeutic intervention in sepsis (reviewed by de Montmollin et al, 2009) and neurodegenerative disorders (McNamee et al, 2010;Ryan et al, 2013).…”
Section: Physiological Relevance Of B 2 -Ar/nf-jb Crosstalkmentioning
confidence: 89%
“…In line with this, b 2 -AR agonists have been proposed as therapeutic intervention in sepsis (reviewed by de Montmollin et al, 2009) and neurodegenerative disorders (McNamee et al, 2010;Ryan et al, 2013).…”
Section: Physiological Relevance Of B 2 -Ar/nf-jb Crosstalkmentioning
confidence: 89%
“…While we present some of the first evidence that anti-inflammatory effects of xamoterol may be ADRB1-mediated, we think that ADRB1 and ADRB2 both have anti-inflammatory actions as the anti-inflammatory effect of the non-selective full agonist, isoproterenol are only partially reversed by each of a selective ADRB1 or ADRB2 antagonist. Indeed others have reported on anti-inflammatory actions of ADRB2, and both receptors should be considered as therapeutic targets (Qian et al 2011; Ryan et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have indicated that the endogenous catecholaminergic transmitter noradrenaline suppresses the inflammatory response and production of neurotoxic substances including TNF‐α, IL‐1β, and NO in the brain (Feinstein et al, ; McNamee, Ryan, Kilroy, & Connor, ; Ryan et al, ). Moreover, noradrenaline negatively regulates the IL‐1 system in glial cells via up‐regulation of IL‐1 receptor antagonist (IL‐1RA) and the IL‐1 receptor, Type ІІ decoy receptor in vitro (McNamee, Ryan, Kilroy, & Connor, ) and in vivo (McNamee, Griffin, Ryan, et al, ) and raises CNS expression of the broad‐spectrum anti‐inflammatory cytokine IL‐10 and its downstream signalling molecule suppressor of cytokine signalling 3 (McNamee, Ryan, Griffin, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Pretreatment with clenbuterol attenuates expression of the pro‐inflammatory molecules IL‐1β, IFN‐γ, and inducible NOS in the kainic acid model of excitotoxicity (Gleeson et al, ) and suppresses NF‐κB activity and expression of the NF‐κB‐inducible genes TNF‐α and ICAM‐1 in response to bacterial LPS (i.c.v.) in rats, whilst concurrently elevating expression of the NF‐κB‐inhibitory protein IκBα (Ryan et al, ). Formoterol is a long‐acting, highly selective β 2 ‐adrenoceptor agonist which, in conjunction with the anti‐inflammatory corticosteroid budesonide, is in clinical use as an FDA‐approved metred dose inhaler for the treatment of asthma and airflow obstruction in patients with chronic obstructive pulmonary disease (Rosenhall et al, ).…”
Section: Introductionmentioning
confidence: 99%